2002
DOI: 10.1136/jcp.55.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor expression in ductal carcinoma in situ of the breast: relation to oestrogen and progesterone receptors

Abstract: Aims: Ductal carcinoma in situ (DCIS) of the breast has been diagnosed increasingly since the advent of mammographic screening. In contrast to the situation in invasive breast carcinoma, there are no reports on androgen receptor (AR) status in DCIS and few reports on oestrogen (ER) and progesterone (PR) receptors. Methods: AR expression was examined in 57 cases of DCIS of the breast and correlated to the degree of differentiation and ER/PR status using immunohistochemical methods. Results: AR positivity was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 20 publications
3
38
1
Order By: Relevance
“…Oestrogen receptor, PR, and AR were positive in 68, 46 and 37% of the patients in our series, respectively. Others found ER, PR, and AR expression in 54 -73, 49 -61, and 33 -44%, respectively (Selim et al, 2002;Baqai and Shousha, 2003;Barnes et al, 2005;Rody et al, 2005). We further found that well-and intermediately differentiated DCISs were predominantly ER positive and PR positive, while poorly differentiated DCIS usually lacked steroid receptor expression and was correlated with Her2 overexpression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Oestrogen receptor, PR, and AR were positive in 68, 46 and 37% of the patients in our series, respectively. Others found ER, PR, and AR expression in 54 -73, 49 -61, and 33 -44%, respectively (Selim et al, 2002;Baqai and Shousha, 2003;Barnes et al, 2005;Rody et al, 2005). We further found that well-and intermediately differentiated DCISs were predominantly ER positive and PR positive, while poorly differentiated DCIS usually lacked steroid receptor expression and was correlated with Her2 overexpression.…”
Section: Discussionmentioning
confidence: 95%
“…Not many studies investigated AR in DCIS. Moinfar et al (2003) reported a higher rate of AR expression in especially low-grade DCIS as opposed to high-grade DCIS, although others did not find a correlation between AR expression and grade (Selim et al, 2002). Androgen receptor-positive breast cancer patients have prolonged survival and a better response to hormonal treatment than AR-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the expression of androgen receptor on cancer cells is often accompanied by the expression of estrogen receptor, and even more frequently progesterone receptor [16][17][18][19]. Therefore many authors maintain that knowing the status of all the three types of steroid receptors will facilitate predicting more accurately the response of patients to hormone therapy [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore many authors maintain that knowing the status of all the three types of steroid receptors will facilitate predicting more accurately the response of patients to hormone therapy [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for estrogen (ER), progesterone (PR), androgen (AR), and vitamin D (VDR) are present in normal human breast and tumor cells (2)(3)(4)(5)(6)(7). The predictive and prognostic significance of ER and PR expression in breast cancer has been elucidated in several recent studies (7,8). In comparison, the significance of AR and VDR expression in human breast tumors is less clear.…”
mentioning
confidence: 99%